Effects of ionizing radiation and different resin composites on shear strength of ceramic brackets: an in vitro study - Amadeu TOMASIN NETO; Flávia AMARAL; Fábio ROMANO (Dental Press Editora, 2022)
ABSTRACT Introduction: Head and neck cancer is considered one of the most common types, and its treatment includes radiotherapy, which can trigger side effects and undesirable sequelae in the oral cavity and dental tissues. Objective: This study aimed to make an in vitro evaluation of the shear strength and failure mode of ceramic orthodontic brackets bonded with two different composites in enamel submitted to ionizing radiation. Methods: After the study was approved by the Research Ethics Committee, 60 healthy human premolars were selected and divided into two groups, based on the absence or presence of ionizing irradiation of the enamel. The fragments were thermocycled and then randomly subdivided into two subgroups, according to the composite used for bonding the ceramic brackets (Inspire Ice - Ormco) to the enamel (n = 15): Transbond XT composite (3M), and Light Bond composite (Reliance). After 24 hours, the specimens were submitted to the shear strength test, and the failure mode was analyzed using a stereomicroscope and confocal microscopy. The shear strength data were submitted to two-way ANOVA, considering a significance level of 5%. Results: The groups submitted to radiation presented lower shear strength values (4.48MPa) than those not irradiated (9.23MPa) (p< 0.001), and the tested composites were not statistically different (p= 0.078). Regarding the fracture mode, all the groups presented mostly adhesive fractures. Conclusion: It was concluded that ionizing radiation negatively affects the adhesion of ceramic brackets, regardless of the composite used for bonding.